PERENCANAAN PRODUKSI DISAGREGAT: STUDI KASUS PRODUKSI PAKAN TERNAK DI PT CHAROEN POKPHAND INDONESIA BALARAJA - Fadlillah, Siti Nur; Widjaja, Thomas (Industrial and Systems Engineering Assessment Journal (INASEA), 2006)
Production planning is an activity to make decison amount product that have to be produce for periods. Production planning is devided by into agregat planning and disagregat planning. Agregat planning is planning on Type and Family level, Disagregat planning on end item level. Disagregat planning used in manufacturing process that have some variance product.Â  Â